COBIT 4.1: AUDIT INFORMATION SYSTEM FINGERPRINT - Mutiana Pratiwi; Ulya Ilhami Arsyah; Aggy Pramana Gusman (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
The development of Information Technology (IT) is currently growing so rapidly. So that the information system has penetrated almost every field of everyday life. There are several types of technology that are usually used by companies, especially to support the human resource management section in managing information in companies and one of them is by implementing technology from an information system regarding attendance. The role of IT in organizational operational processes, the Cooperative Industry and Trade office uses a fingerprint record system for taking attendance. The attendance-taking tool has a sophisticated electronic system that only reads the fingerprint patterns of each employee. With this fingerprint attendance, employees can be motivated to arrive early because fingerprint attendance cannot manipulate employee attendance in the office. This study uses the COBIT 4.1 method which focuses on the DS (Delivery and Support), and ME (Monitor and Evaluate) domains. By calculating the maturity level, the DS value of 4.58 is obtained at level 5, namely Optimized Level, which means that agencies have implemented information technology very well and agencies need to maintain system stability so that it continues to develop, while the ME calculated on a scale of 3.99 is at the level 4, namely managed level, which means that security in the system is quite good and only needs to be evaluated so that the vision and mission of the agency are achieved.